Transnational networks of insurgency and crime: explaining the spread of commercial insurgencies beyond state borders (2015)
The concept of commercial insurgency describes organisations permeated by criminal interests, especially when they participate in the production and trade of specific commodities. This article introduces a framework of analysis to explain how such organisations exploit elements through their region in order to embed militants beyond the borders of a single state. Through the construction of transnational networks, insurgents are able to perform political, military, and criminal activities, which not only contribute to the organisation's goal, but which also provide an opportunity for the insurgency to survive when the counterinsurgent offensive is strong within the primary theatre. This is a clear challenge for the state. © 2014 Taylor and Francis.